Subsidies - Reble, John E. (My University, 1947)
The interrelationship of the social, economic and political life of our Western civilization is an evident reality. A thesis on this relationship, existing as it does even in Canada, would be a tremendous task. However, a specific topic relating to the complementary forces of these three factors presents a much less laborious and less complex work. One such specialized topic is the subject of this thesis, namely, the use of subsidies by a government in their political, economic and social environment. Insufficient attention has been given in the past to the economics development of the principles and effects of subsidies. Numerous articles have been written on the specific use or uses of a subsidy (as for example an article on the advisability of giving a subsidy in this past war to increase the production of certain farm commodities), yet when it comes to writings on the principle, the incidence and the effects of subsidies, a dearth of material exists. Because of the steadily increasing use of this form of government assistance since 1929 greater attention should be directed to the basic principles of subsidization. The prime purpose of this thesis therefore is an enquiry into such principles as well as an evaluation or the economic and social advisability of subsidies used in connection with their various motives. There are two further considerations which should be made. First, the possibility that the economic and social factors arising from the use of subsidies are pulling in opposite directions thereby making it necessary to weigh the value of the economic effects against the value of the social effects. Secondly, the possibility that these factors are working in similar directions. It is secondary purpose of this study to indicate which of these two cases exists.
Keywords: Political Economy